Coccinella sptumpumctata (Coccinellidae: Coleoptera) as a predator of cecidozoan, hymenopteran and dipteran in Garhwal Himalaya, India - V. K. Rawat (Environment Conservation Journal, 2011)
The gall forming insects (cecidozoan), Allirhytis semicarpifoliae, Rhopalomyia baijali Labopteromyia bivalve and Amaradiplosis amaermyia, Andricus sp. are widely distributed in Garhwal Himalaya causing galls on different economically important plants. In this regard, out of theses Coccinellids oftenly crawl on gall bearing portions in search of their prey, but it is frequently seen in case of grubs. Maximum numbers of grubs prefer to feed upon the larvae of R. baijali. The abundance of predators synchronized with peak population of prey insects. The relative abundance of predators always higher in tropical region than those of other geographical zones. The grubs of Coccinellids find their way by cutting the gallicolous tissues with help of their serrated mandibles so as to secure their prey inside the gall. Experiments on feeding propensity of grubs of Coccinella saptempunctata show that this insect devour 15.2 to 22.8 larvae of R. baijali per 24 hrs. in laboratory condition (Table-1). It was also noticed that the predatory activity was recorded high in the lower altitude in comparision to the higher one.